Cultivation and application of natural nutrients in fishing farms (Texas Journal of Agriculture and Biological Sciences, 2023)
This article explores the importance of the cultivation and use of natural nutrients in fish farms. It studies the potential benefits of applying sustainable practices such as organic nutrient and nutrient management techniques to improve fish health and optimize aquaculture operations. In the methods section, various approaches to the introduction of natural nutrients are indicated, the results, discussions and conclusions sections analyze the advantages and provide recommendations for the future